Association between maternal cardiometabolic markers and fetal growth in non-complicated pregnancies: a secondary analysis of the PRINCESA cohort - Isabel Omaña-Guzmán; Luis Ortiz-Hernández; Monica Ancira-Moreno; Myrna Godines-Enriquez; Marie O’Neill; Felipe Vadillo-Ortega (Scientific Reports, 2024)
Abstract The objective of this study was to evaluate the association of maternal cardiometabolic markers trajectories (glucose, triglycerides (TG), total cholesterol, systolic blood pressure (SBP) and diastolic blood pressure (DBP)) with estimated fetal weight trajectories and birth weight in Mexican pregnant women without medical complications. Cardiometabolic marker trajectories were characterized using group-based trajectory models. Mixed-effect and linear regression models were estimated to assess the association of maternal trajectories with estimated fetal weight and birth weight. The final sample comprised 606 mother–child dyads. Two trajectory groups of maternal cardiometabolic risk indicators during pregnancy were identified (high and low). Fetuses from women with higher values of TG had higher weight gain during pregnancy ( $$\hat{β }$$ β ^ = 24.00 g; 95%CI: 12.9, 35.3), were heavier at the sixth month ( $$\widehat{β }$$ β ^ =48.24 g; 95%CI: 7.2, 89.7) and had higher birth weight ( $$\widehat{β }$$ β ^ = 89.08 g; 95%CI: 20.8, 157.4) than fetuses in the low values trajectory. Fetuses from mothers with high SBP and DBP had less weight in the sixth month of pregnancy ( $$\widehat{β }$$ β ^ = − 42.4 g; 95%CI: − 82.7, − 2.1 and $$\widehat{β }$$ β ^ = − 50.35 g; 95%CI: − 94.2, − 6.4), and a higher DBP trajectory was associated with lower birth weight ( $$\widehat{β }$$ β ^ = − 101.48 g; 95%CI: − 176.5, − 26.4). In conclusion, a longitudinal exposition to high values of TG and BP was associated with potentially adverse effects on fetal growth. These findings support the potential modulation of children’s phenotype by maternal cardiometabolic conditions in pregnancies without medical complications.